2016
DOI: 10.21091/mppa.2016.3027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Maximum Aerobic Capacity and Anaerobic Threshold of Elite Ballet Dancers

Abstract: Abstract:An athlete's cardiorespiratory profile, maximal aerobic capacity and anaerobic threshold, is affected by their training regimen and competition demands. The purpose of the present study is to ascertain whether there are company rank differences in maximal aerobic capacity and anaerobic threshold in elite classical ballet dancers. Seventy-four volunteers (M=34, F=40) were recruited from two full-time professional classical ballet companies. All participants completed a continuous incremental treadmill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
1
15
3
Order By: Relevance
“…In the present study, both group and overall mean VO2peak values are higher than those previously reported for contemporary dance students, as reviewed by Angioi et al 5 ( Table 2). Such comparison is not directly available for AT values, although values from various other dance genres for adult professionals and students range from 73.9 -85.1 %VO2peak, 19,25,26 which is lower than the overall mean in the present study ( Table 2). Higher scores were also found in individual criteria and total scores in the ACM than previous studies using the same measure 3,4 (Table 3).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In the present study, both group and overall mean VO2peak values are higher than those previously reported for contemporary dance students, as reviewed by Angioi et al 5 ( Table 2). Such comparison is not directly available for AT values, although values from various other dance genres for adult professionals and students range from 73.9 -85.1 %VO2peak, 19,25,26 which is lower than the overall mean in the present study ( Table 2). Higher scores were also found in individual criteria and total scores in the ACM than previous studies using the same measure 3,4 (Table 3).…”
Section: Discussioncontrasting
confidence: 61%
“…20 Through the previous body of available literature, the extent to which a dancers' cardiorespiratory fitness level is directly related to the performance ability of that dancer is not all-together clear. It seems that professional dancers, and higher ranked professionals in ballet, have greater cardiorespiratory capacity than students, 5,20 and lower ranked professionals in ballet, [17][18][19] but correlational studies have found no significant relationship between aerobic fitness measures and measures of aesthetic competence. 4,8 A number of benefits to higher cardiorespiratory fitness levels amongst dancers are seen to exist; however, we are currently only at the beginning of our understanding of how this translates in an individual dancer's outwardly visible skill and overall performance ability.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The peak VO 2 data from the treadmill test in this study was at the upper limits or greater than that reported by dancers in other genres. Previous studies have reported male dancers ranging between 50-57 mL/kg/min and female 40-47 mL/kg/min for ballet and contemporary dance, 18,23 though higher scores have been published for dancesport competitors (males 60 mL/kg/min; females 52 mL/kg/min). 21 Similar to other dance genres, hip-hop dancers do not do a lot of additional supplemental training alongside their dance training.…”
Section: Discussionmentioning
confidence: 93%
“…3 There has been little scientific research on whether there are physiological, biomechanical, or psychological differences between the dance genres. The majority of studies have examined individual genres usually focusing on the different dance formats (class, rehearsal, or performance) [4][5][6][7][8][9][10][11][12] or physical fitness characteristics of its dancers, 9,[13][14][15][16][17][18] though a few studies have directly compared different genres. [19][20][21][22] Often dancers are trained in the main genres (ballet, contemporary, and jazz) during their vocational training, and being able to isolate the effect of one genre compared to another is only possible in elite adult dancers.…”
mentioning
confidence: 99%